Γράμμα του οικουμενικού πατριάρχη Ιωακείμ Α΄ (1498, Αύγ.) για τα πατριαρχικά σταυροπήγια στη Θεσσαλία . Επίμετρο: Και πάλι για την ανασύσταση της Επισκοπής Γαρδικίου - ΑΓΟΡΙΤΣΑΣ Δημήτρης (Byzantina Symmeikta, 2019)
Letter of the Ecumenical Patriarch Joachim I (1498, Aug.) Concerning The Patriarchal Stauropegia in Thessaly. (with an appendix on the Bishopric of Gardikion) In this article an unknown letter of Patriarch Joachim I, concerning the patriarchal stauropegia in Thessaly, is published and commented. The letter is addressed to the ecclesiastical authorities of the Bishopric of Stagoi and the Metropolis of Larissa.It deals with issues related to the patriarchal stauropegia of Thessaly, the payment to the Patriarchate of the so called charatzion, as well as their relations with the Metropolitan of Larissa. The afore-mentioned document is of particular importance as it identifies the time when Dionysios I was metropolitan of Larissa and mentions by name seven patriarchal stauropegia in Thessaly.